Country differences in the relationship between incomes and wage rates of working partners - Anja-Kristin Abendroth (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This paper investigates the relevance of the cultural and economic country context for differences in the effect of male partner income on female income and wage rate for 9,373 respondents in 13 European countries. Data taken from the European Community and Household Panel (ECHP), which comprises information on partner income trends between 1994 and 2001, were used to estimate fixed effect models. We find differences between countries in the effect of male partner income on women's income. In countries where average male salaries represent high purchasing power, male partner income has a negative influence on female income and wages. Less evidence was found for the argument that also gender cultures moderate partner income effects.
Keywords: 330